2021
DOI: 10.3390/cancers13112701
|View full text |Cite
|
Sign up to set email alerts
|

The Critical Role of TRIB2 in Cancer and Therapy Resistance

Abstract: The Tribbles pseudokinases family consists of TRIB1, TRIB2, TRIB3 and STK40 and, although evolutionarily conserved, they have distinctive characteristics. Tribbles members are expressed in a context and cell compartment-dependent manner. For example, TRIB1 and TRIB2 have potent oncogenic activities in vertebrate cells. Since the identification of Tribbles proteins as modulators of multiple signalling pathways, recent studies have linked their expression with several pathologies, including cancer. Tribbles prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 109 publications
(178 reference statements)
1
24
0
Order By: Relevance
“…Tribbles pseudokinase 2 (TRIB2) is a member of the tribbles family ( 8 ). TRIB2 includes an N-terminal domain, a C-terminal domain and a central pseudokinase domain.…”
Section: Introductionmentioning
confidence: 99%
“…Tribbles pseudokinase 2 (TRIB2) is a member of the tribbles family ( 8 ). TRIB2 includes an N-terminal domain, a C-terminal domain and a central pseudokinase domain.…”
Section: Introductionmentioning
confidence: 99%
“…While not previously described as binding partners, the mTOR regulatory subunits RICTOR and RAPTOR were also detected in the TRIB2 interactome ( Figure 1 C). Previous studies have shown, however, that TRIB2 regulates mTOR signaling [ 42 , 43 ]. Interactions that have not been described earlier included the interaction between TRIB3 and the mitochondrial transporter TIM-TOM complex, a complex found in the mitochondrial membrane that transports proteins into the inner membrane of the mitochondria [ 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…Tribbles 2 (TRIB2) is a cancer-associated pseudokinase with a diverse interactome, includes MEK1 and AKT as binding partners. There is substantial evidence that human TRIB2 promotes survival and drug resistance in solid tumors (Ferreira et al, 2021;Mayoral-Varo et al, 2021) and hematological cancers (Stein et al, 2015) and therefore is of interest as a therapeutic target. The TRIB2 destabilizing agent afatinib (34) caused rapid TRIB2 degradation in human AML cancer cells (Foulkes et al, 2018) providing the proof of concept for the druggability of the TRIB2 oncoprotein.…”
Section: Chart 5 Chemical Structures Of Her Modulators (29-31)mentioning
confidence: 99%